The patrons and their poor: Jewish community and public charity in early modern Germany - Ḳaplan, Devorah (Jewish Culture and Contexts, 2020)
Debra Kaplan offers the first extensive analysis of Jewish poor relief in early modern German cities and towns, exploring the intersections between various sectors of the populations--from wealthy patrons to the homeless and stateless poor--providing an intimate portrait of the early modern Ashkenazic community.